2018
DOI: 10.5120/ijca2018917057
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Student Academic Performance using Neural Network, Linear Regression and Support Vector Regression: A Case Study

Abstract: Predicting students" academic performance is very crucial especially for higher educational institutions. This paper designed an application to assist higher education institutions to predict their students" academic performance at an early stage before graduation and decrease students" dropout. The performance of the students was measured based on cumulative grade point average (CGPA) at semester eight. The students" course scores for core and non-core courses from the first semester to the sixth semester are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…It is noticeable in Table V that NB and NN have the lowest prediction error. Through counts, it can determine that NB only has seventeen (17) prediction error while NN has a total of eighteen (18) prediction error. Thus, it is now harder to decide which among the two classification algorithms is better since there is only 0.56% of difference in terms of prediction error between them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noticeable in Table V that NB and NN have the lowest prediction error. Through counts, it can determine that NB only has seventeen (17) prediction error while NN has a total of eighteen (18) prediction error. Thus, it is now harder to decide which among the two classification algorithms is better since there is only 0.56% of difference in terms of prediction error between them.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, unlike NB, LR assumes that the dependent variables are related to the independent variables or the class in a linear manner. Stated in the study of Bum et al [17] that LR is the quickest machine learning algorithm in developing model without compromising the accuracy of its prediction hence, it was proven on the experiment of research [18] after comparing the results of shortest time in building model and prediction accuracy to another two sophisticated machine learning algorithms (NN and support vector regressor). In this manner, LR can be used through this formula: y=B0+B1*x1 where y is the class and x are the independent variables.…”
Section: ) Linear Regressionmentioning
confidence: 99%
“…Previous studies in Bangladesh observed that RF algorithms were the best predictors in terms of accuracy when predicting childhood anemia, while SVM identified some important characteristics when used to predict the status of child diarrhea in Bangladesh (Khan et al, 2019;Maniruzzaman and Abedin, 2020). In a different context, neural networks were poorer at predicting student academic performance than linear regression and support vector regression (Obsie and Adem, 2018). In another study, evidence from early childhood asthma persistence (Bose et al, 2021) and early childhood obesity (Pang et al, 2021) and researchers observed that XGBoost was found to be one of the best performing models in their study.…”
Section: Discussionmentioning
confidence: 95%
“…Belachew and Gobena's (2017) results were supported by the paper written by Jayaprakash, Balamurugan, and Chandar (2018). However, Obsie and Adem (2018) found that Linear Regression and Support Vector Regression were better than Neural Networks. Also, Acharya and Sinha (2014) found that the decision tree class of algorithms was the best.…”
Section: Literature Reviewmentioning
confidence: 98%